2021
DOI: 10.1111/hel.12832
|View full text |Cite
|
Sign up to set email alerts
|

Application of WeChat platform in the management of patients infected with Helicobacter pylori

Abstract: Objective To evaluate the effectiveness of using WeChat platform to manage the patients with H. pylori infection. Methods 566 patients were randomly divided into two groups: The control group was treated with traditional management method, and the experimental group established WeChat group and implemented the informatization management. The two groups were given a unified plan to eradicate H. pylori. After the treatment, the C14 breath test was reexamined. The follow‐up rate and H. pylori eradication rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 6 publications
0
45
2
Order By: Relevance
“…Regarding blinding, 3 studies 20,22,24 described methods for single blinding, one study 27 was open trial (non‐blind), and the remaining 5 studies 21,23,25,26,28 were judged as unclear risk due to insufficient information. With respect to attrition bias, one study conducted by Ma et al 28 was judged as high risk of bias due to the unbalanced proportion of missing data, and all the remaining studies were judged as low risk of bias. All studies had low risks of bias based on selective reporting (reporting bias), and other sources of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding blinding, 3 studies 20,22,24 described methods for single blinding, one study 27 was open trial (non‐blind), and the remaining 5 studies 21,23,25,26,28 were judged as unclear risk due to insufficient information. With respect to attrition bias, one study conducted by Ma et al 28 was judged as high risk of bias due to the unbalanced proportion of missing data, and all the remaining studies were judged as low risk of bias. All studies had low risks of bias based on selective reporting (reporting bias), and other sources of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the complexity and long duration of current H . pylori eradication regimens, which may affect patient compliance, increasing clinical studies 20‐28 have attempted to use these EPI methods to improve H . pylori eradication rate.…”
Section: Discussionmentioning
confidence: 99%
“…In individual trials, sample sizes ranged from 80 to 566 (a total of 1599 participants across all studies). Of the seven RCTs, two 22,23 were from Western countries (England and Australia), while the remaining five 16,24–27 were from China. All seven studies 16,22–27 reported on the eradication rate of H .…”
Section: Resultsmentioning
confidence: 99%
“…pylori patients tend to have low medication compliance, thus affecting the eradication rate. In this regard, research has shown that patient compliance can be improved through strengthened educational provisions, thus enhancing the treatment effects 16 …”
Section: Introductionmentioning
confidence: 99%
“…Compliance is an important factor influencing the eradication rate of H. pylori . Several studies ( 41 43 ) were conducted in China to evaluate useful methods to improve compliance in the management of H. pylori infection. Interestingly, short-message-based reeducation or WeChat platform (a social media platform) reminders two times daily were the efficient ways to improve the eradication rate of H. pylori infection and elevate the compliance of H. pylori regimens.…”
Section: Discussionmentioning
confidence: 99%